Kompetensi Kepribadian Guru Pendidikan Agama Islam Perspektif Al-Ghazali di SMA/SMK Negeri Kota Tarakan - Baharuddin Baharuddin; Adian Husaini (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2021)
Teachers' certification as a medium to improve teacher competence is considered not optimal, so it is necessary to explore a more comprehensive concept. This study aimed to examine the Personality Competency of Islamic Religious Education Teachers (PAI) at Tarakan State High School/Vocational High School in al-Ghazali Perspective. This research is field research that is descriptive qualitative. This research approach is a theological, pedagogical, psychological, and managerial approach. This study's data sources are primary data sources consisting of principals, deputy heads, Islamic Education teachers, learners, and secondary data sources consisting of the necessary documentation. Research instruments use observation guides, interview guidelines, and checklist documentation. Data collection methods use observation, interviews, and documentation. Data processing and analysis techniques through three stages, namely data reduction, data presentation (data display), and conclusion withdrawal (data verification). Through collecting, processing, and analyzing data, it was found that in general aspects of the personality of Islamic Education teachers in Tarakan City in al-Ghazali Perspective still exist that need to be improved from less to good. The implication is: Teachers must have the right criteria, as stated by Al-Ghazali and the LawAbstrakSertifikasi guru sebagai media untuk meningkatkan kompetensi guru, dinilai belum optimal, sehingga perlu untuk menggali sebuah konsep yang lebih komprehensif. Tujuan penelitian ini mengkaji Kompetensi Kepribadian Guru Pendidikan Agama Islam (PAI) di SMA/SMK Negeri Kota Tarakan dalam Perspektif al-Ghazali. Penelitian ini adalah penelitian lapangan yang bersifat deskriptif kualitatif. Pendekatan penelitian ini adalah pendekatan teologis, pedagogis, psikologis, dan pendekatan manajerial. Sumber data dalam penelitian ini yaitu sumber data primer yang terdiri dari kepala sekolah, wakil kepala, guru Pendidikan Agama Islam, peserta didik, dan sumber data sekunder yang terdiri dari dokumentasi penting. Instrumen penelitian menggunakan panduan observasi, pedoman wawancara, dan check list dokumentasi. Metode pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Adapun teknik pengolahan dan analisis data melalui tiga tahap, yaitu reduksi data, penyajian data (display data), dan penarikan kesimpulan (verifikasi data). Melalui proses pengumpulan, pengolahan, dan analisis data maka ditemukan hasil penelitian bahwa pada umumnya aspek kepribadian guru Pendidikan Agama Islam di Kota Tarakan dalam Perspektif al-Ghazali masih ada yang perlu ditingkatkan dari kurang baik menjadi baik. Implikasinya adalah: Guru harus memiliki kriteria baik sebagaimana telah diungkapkan oleh Al-Ghazali dan Undang-Undang.